Post-Merger Community Perception of Bank Syari’ah Indonesia - Imahda Khoiri Furqon; Fitri Kurniawati (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2023)
his research seeks to uncover phenomena in society regarding promotions carried out by Bank Syari'ah Indonesia (BSI) after the merger. As is well known, BRI Syari'ah, BNI Syari'ah and Syari'ah Mandiri Bank merged early last year, but the effect has not been very visible in society. For this reason, this research was conducted to analyze public perceptions regarding BSI's post-merger promotion. The data used is primary data. The data sources for this research are the general public, students, lecturers and teaching staff who have or have not become customers of BSI. Data collection is done by interviews and documentation. The results obtained were analyzed using phenomenological-descriptive analysis techniques. The findings of this study are that the perception of the people of Pekalongan towards Bank Syari'ah Indonesia after the merger process is quite good. The community fully supports this merger step, because many positive effects are felt by the community. Meanwhile, the influence of the promotion on the interest in saving in Pekalongan society after the merger at Bank Syariah Indonesia was also quite significant, in line with the increasing public trust in BSI, but there are still those who don’t save either